2007
DOI: 10.1037/0022-0663.99.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Are teachers' expectations different for racial minority than for European American students? A meta-analysis.

Abstract: Four quantitative meta-analyses examined whether teachers' expectations, referrals, positive and neutral speech, and negative speech differed toward ethnic minority students (i.e., African American, Asian American, and Latino/a) as compared with European American students. Teachers were found to hold the highest expectations for Asian American students (d = -.17). In addition, teachers held more positive expectations for European American students than for Latino/a (d =.46) or African American (d =.25) student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
401
5
19

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 635 publications
(442 citation statements)
references
References 79 publications
17
401
5
19
Order By: Relevance
“…Participants may have consciously wanted to be more lenient on Black than White candidates. For example, in adopting this affirmative action criterion, participants may have been deliberately attempting to counter perceived historical disadvantages, perceived disadvantages in academic experience, perceived differences in diagnosticity of academic scores, or perceived cultural biases (e.g., Abrams, Bertrand & Mullainathan, 2012;Tenenbaum & Ruck, 2007). Alternatively, they may have been trying to correct underrepresentation of Blacks in academic advancement, or was the result of attitudinal preferences for Blacks over Whites.…”
Section: Discussionmentioning
confidence: 99%
“…Participants may have consciously wanted to be more lenient on Black than White candidates. For example, in adopting this affirmative action criterion, participants may have been deliberately attempting to counter perceived historical disadvantages, perceived disadvantages in academic experience, perceived differences in diagnosticity of academic scores, or perceived cultural biases (e.g., Abrams, Bertrand & Mullainathan, 2012;Tenenbaum & Ruck, 2007). Alternatively, they may have been trying to correct underrepresentation of Blacks in academic advancement, or was the result of attitudinal preferences for Blacks over Whites.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Jussim and Harber (2005) conclude that teachers are not biased because the differences in teacher expectations for stigmatized demographic student subgroups closely correspond to differences in those groups' academic performance in previous grades and achievement tests. However, a substantial number of studies published after Jussim and Harber's (2005) review have found significant differences in teacher expectations for students of different demographic groups after the previous performance of students was controlled for (e.g., Glock and Krolak-Schwerdt 2013;McKown and Weinstein 2008;Rubie-Davies et al 2006;Speybroeck et al 2012;Tenenbaum and Ruck 2007;van den Bergh et al 2010). Generally, for students with equal performance records, teachers tend to have lower expectations for future academic performance when the student comes from a less affluent family and when the student is a boy.…”
Section: Teacher Expectationsmentioning
confidence: 99%
“…For example, trainee teachers in Singapore tended to ascribe positive stereotypes to Chinese students (e.g., industrious) and negative stereotypes to Malay students (e.g., lazy; Khoo & Lim, 2004). While the effect of such stereotypes on academic achievement in Singapore is currently unknown, four meta-analyses in the United States suggested that teachers' expectations vary depending on the race of the student (Tenenbaum & Ruck, 2007) and that these expectations have a negative effect on racial minorities' academic achievement (McKown & Weinstein, 2008;Rubie-Davies, Hattie, & Hamilton, 2006).…”
Section: Endorsement Of Meritocracymentioning
confidence: 99%